Assessing Household Vulnerability to Employment Shocks: A Simulation Methodology Applied to Bosnia and Herzegovina - Luigi Cuna (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
Household vulnerability relates to the incapacity of a household to preserve its welfare because of negative events. In Bosnia and Herzegovina, vulnerability is a central issue in the policy debate: many households are at risk of poverty due to fragile livelihood systems or high exposure to shocks. Since no panel data are available in Bosnia and Herzegovina, a micro-simulation methodology is adopted on the basis of a household consumption model based on quintile regression. Shocks are simulated in the labour market and the methodology consents the identification of the typologies of households which suffer from severe welfare losses or that are plunged into poverty after the shocks. The results show that the vulnerable households identified change when different shocks or a diverse definition of vulnerability are taken into consideration. At the same time, the characteristics of households vulnerable to poverty are shown to be different with respect to those of the poor.
Keywords: 330; Armut; Privater Haushalt; Arbeitslosigkeit; Schock; Simulation; Bosnien-Herzegowina